A Case Study in Sleman: A Feasibility Analysis of Rice-Fish Farming Based on Resources Productivity - Triyono; Alvaseno, Dafit (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
One of the efforts to optimize resources in order to increase farm income is mina rice, which is rice and fish farming on one land and season in an integrated manner. This study aims to determine the cost, revenue, income, and profit of rice-fish farming. In addition, this study aims to determine the feasibility of rice-fish farming through a resource productivity approach. The method used is descriptive analysis, by taking respondents as many as 35 farmers in Samberembe village, Candibinangun, Pakem, Sleman, and the Special Region of Yogyakarta. The results of the study showed that the average paddy-fish farming area of 1,063 square meters requires an average total cost incurred for one year for production is IDR. 27,591,910.95. Rice-fish farming revenue amounted to IDR. 36,293,686, so that the income obtained amounted to IDR. 21,590,063.81. Meanwhile, the profit of rice-fish farming amounted to IDR. 8,701,774.77 for three seasons per year. The results of the feasibility analysis showed an R/C value of 1.3, a capital productivity value of 62% per year, and a labor productivity value of IDR. 206,125.21 per full time day, and a land productivity value of IDR. 7,292.00 per square meter. These results indicate that rice-fish farming is feasible to develop.